A New Species of Danioid Fish (Danionidae, Chedrinae) from Imphal River, North-Eastern India - L. Arunkumar; M. Thoibi (Zoodiversity)
Barilius imphalensis sp. n. is described from the Imphal River, a main head-water tributary of Chindwin River basin in Manipur, a hill grit state of North-Eastern India. It is distinguished from all its congeners in having the following combination of characters: absence of barbels, presence of tubercles on the tip of snout, presence of dentary tubercles, presence of complete lateral lines with 41 scales, pre-dorsal scales 18, head depth at supra-occipital 20.2–23.4 % SL, body depth at dorsal fin origin 25.0–28.1 % SL, pre-anal length 65.1–68.5 % SL, height of dorsal fin 22.9–24.8 % SL, height of anal fin 26.1–28.9 % SL, eye diameter 6.3–6.9 % SL and 26.2–26.8 % HL, inter-orbital width 32.3–38.5 % HL and short blue vertical bars along the body 15–17. Key to species of the genus Barilius of the north-eastern India and their distribution pattern in the six different river drainage systems are provided.